A Case Report of Subacute Thyroiditis following mRNA COVID-19 Vaccine. (11th November 2021) - Plaza-Enriquez, Leidy; Khatiwada, P.; Sanchez-Valenzuela, M.; Sikha, A.
Abstract : Background . Subacute thyroiditis has been reported after administration of influenza vaccine. We describe a case of a patient who developed subacute thyroiditis after administration of. Moderna mRNA COVID-19 vaccine. Case Presentation . A 42-year-old female, with a past medical history of stage IIIB pT3N1aM0 right adenocarcinoma of colon status, after right hemicolectomy on 01/2020, followed by adjuvant chemotherapy, paroxysmal supraventricular tachycardia, iron deficiency anemia, chemotherapy-induced neuropathy, and lumbar radiculopathy, presented to our clinic with anterior neck pain that started 6 days after the second dose of Moderna mRNA COVID-19 vaccine. She was diagnosed with subacute thyroiditis and treated conservatively with pain medications. Conclusion . Subacute thyroiditis could represent one of the side effects of Moderna mRNA COVID-19 vaccine. Further reports are lacking.